2019
DOI: 10.1177/2055102919848572
|View full text |Cite
|
Sign up to set email alerts
|

Dispositional forgiveness and stress as primary correlates of executive functioning in adults

Abstract: The purpose of this study was to explore the physical, social, and mental health correlates of executive functioning in adults. Our sample consisted of 250 adults aged 18–55 years who participated in a survey. Participants reported on their physical health behaviors, family closeness, and mental health. Using hierarchical linear regression, the final model explained 41 percent of executive functioning in adults. Dispositional forgiveness of situations, stress, and living in a single-family home were the only s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Forgiveness provides for transformation of negative feelings, thoughts and behaviors to neutral or positive ones, and it reduces stress ( Chi et al., 2019 ; Worthington and Scherer, 2004 ). Empirical research on stress and coping and their correlates, revealed strong relationships with forgiveness ( Crandall et al., 2019 ; Gall and Bilodeau, 2021 ; Ochu et al., 2018 ) which are differentiated by gender, age and culture. Many studies have consistently shown that women experience more chronic, traumatic and minor daily stress ( Matud, 2004 ; Olff et al., 2007 ; Street and Dardis, 2018 ) when compared to men.…”
Section: Introductionmentioning
confidence: 99%
“…Forgiveness provides for transformation of negative feelings, thoughts and behaviors to neutral or positive ones, and it reduces stress ( Chi et al., 2019 ; Worthington and Scherer, 2004 ). Empirical research on stress and coping and their correlates, revealed strong relationships with forgiveness ( Crandall et al., 2019 ; Gall and Bilodeau, 2021 ; Ochu et al., 2018 ) which are differentiated by gender, age and culture. Many studies have consistently shown that women experience more chronic, traumatic and minor daily stress ( Matud, 2004 ; Olff et al., 2007 ; Street and Dardis, 2018 ) when compared to men.…”
Section: Introductionmentioning
confidence: 99%
“…The studies (Baskin & Enright, 2004;Crandall et al, 2019;Lijo, 2018;Ursua & Valdes, 2018) found that forgiveness was positively correlated with mental health.…”
Section: Resultsmentioning
confidence: 99%
“…I n recent years, scholars have significantly increased their research interest in the problem of forgiveness (Asici, 2019;Crandall et al, 2019;Karduz & Saricam, 2018). The authors believe that the tendency to forgive is one of the essential factors of mental health.…”
Section: Introductionmentioning
confidence: 99%